2005
DOI: 10.1021/ct050173k
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic DFT Calculation of 119Sn Chemical Shifts and Coupling Constants in Tin Compounds

Abstract: The nuclear shielding and spin-spin coupling constants of (119)Sn in stannane, tetramethylstannane, methyltin halides Me4-nSnXn (X = Cl, Br, I; n = 1-3), tin halides, and some stannyl cations have been investigated computationally by DFT methods and Slater all-electron basis sets, including relativistic effects by means of the zeroth order regular approximation (ZORA) method up to spin-orbit coupling. Calculated (119)Sn chemical shifts generally correlate well with experimental values, except when several heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
79
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 90 publications
(103 reference statements)
11
79
0
Order By: Relevance
“…Some of them were proposed based on theoretical calculations [7][8][9][10][11][12][13] and others based on a mixture between spin-rotation measurements and theoretical calculations of free atoms.…”
Section: 6mentioning
confidence: 99%
“…Some of them were proposed based on theoretical calculations [7][8][9][10][11][12][13] and others based on a mixture between spin-rotation measurements and theoretical calculations of free atoms.…”
Section: 6mentioning
confidence: 99%
“…Chemical shifts can be accurately predicted even at the nonrelativistic level due to error compensation in the calculated shielding constants, [24][25][26][27][28] provided no other heavy atoms are bound to tin. [29,30] Regarding the calculation of the coupling constants it has been shown that even for moderately heavy nuclei scalar relativistic effects are not negligible. [31,32] In this context relativistic ZORA DFT calculation of n J( 119 Sn,X) (n = 1,2; X = 1 H, 13 C) have been reported [29,33,34] [35] allowed to correlate these couplings with the θ angle of the dimethylti-n(IV) moiety even in those cases where the aforementioned Lockhart-Manders equations fail.…”
Section: Introductionmentioning
confidence: 99%
“…[29,30] Regarding the calculation of the coupling constants it has been shown that even for moderately heavy nuclei scalar relativistic effects are not negligible. [31,32] In this context relativistic ZORA DFT calculation of n J( 119 Sn,X) (n = 1,2; X = 1 H, 13 C) have been reported [29,33,34] [35] allowed to correlate these couplings with the θ angle of the dimethylti-n(IV) moiety even in those cases where the aforementioned Lockhart-Manders equations fail. [12] Again, a systematic error compensation might be at the root of the observed good agreement.…”
Section: Introductionmentioning
confidence: 99%
“…Wiley-VCH ZAAC 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 The shortest distances for heteronuclear and homonuclear pairs of nuclei reported for the X-ray structure [1] As a third contribution to line broadening, J-couplings have to be taken into account for 119 Sn, since it has been documented previously [9][10][11][12][13][14][15][16][17][18][19][20][21] that they may also be of the order of kHz. In fact, the J-couplings for 119 Sn can be so large that it has been possible to determine the anisotropy of this interaction in some organo-tin compounds [14] by using off-magic angle spinning.…”
Section: Page 4 Of 20mentioning
confidence: 99%
“…Unlike dipolar couplings, which act through space, J-couplings are mediated by covalent bonds, and are difficult to observe in solid-state NMR, because they are usually much smaller than dipolar couplings [6][7][8]. For 119 Sn however, J-couplings tend to be comparatively large (in the range of kHz), and have been reported before in the literature for a variety of compounds [9][10][11][12][13][14][15][16][17][18][19][20][21]. The existence of J-couplings in α-SnF 2 shown here is further evidence for the existence of covalent Sn-F bonds in tin(II) fluoride.…”
Section: Introductionmentioning
confidence: 99%